Induction of alopecia areata in C3H/HeJ mice using cryopreserved lymphocytes. Issue 3 (June 2021) - Hashimoto, Kei; Yamada, Yoshihito; Sekiguchi, Kota; Matsuda, Shoichi; Mori, Sachi; Matsumoto, Tatsumi
Highlights: We report a new method to generate AA model using cryopreserved lymphocytes. AA mice have similar pathological characteristics to AA patients. Effector memory T cells and dendritic cells contribute to a higher AA incidence. Abstract: Background: Alopecia areata (AA) is an autoimmune disease resulting in non-scarring hair loss. Animal models are useful means to identify candidates for therapeutic agents. The C3H/HeJ mouse AA model induced via transferring cultured lymphoid cells isolated from AA-affected mice is widely used for AA research. However, this conventional method requires the continuous breeding of AA mice. Objective: We aimed to establish a new method to generate AA model using the transfer of cryopreserved cells, which allows the rapid induction of a large number of AA mice when needed. Methods: We cryopreserved lymph node cells soon after isolation from AA-affected mice and injected thawed-cultured cells into recipient mice. H&E staining, immunohistochemical staining, quantitative real-time PCR and ELISA were conducted to identify pathological characteristics. Flow cytometry was performed to reveal the profile of transferred cells. Results: More than 90 % of recipient mice developed AA-like hair loss and showed inflammatory cell infiltration around anagen hair follicles, markedly increased mRNA expressions of interferon-γ, CXCL11, and granzyme B, and elevated interferon-α protein levels in the skin compared with naïve mice. Higher percentages of effector memory T cells and dendritic cells in transferred cells resulted in a higher incidence of AA. Conclusion: This is the first report to establish a method for generating AA mice using cryopreserved lymphocytes. These AA mice have similar pathological characteristics to AA mice generated with the conventional method and AA patients. This convenient and reproducible method is expected to be valuable for AA study.